Heart rhythm disturbances after high-dose chemotherapy followed by haematopoietic stem cell transplantation in a patient with refractory germ cell cancer - Młot, Beata; Rzepecki, Piotr (Contemporary Oncology/Współczesna Onkologia, 2010)
Testicular cancer, although an uncommon malignancy, is the most frequently occurring cancer in young men. Most testicular tumours are of germ-cell origin. Approximately 20% to 30% of patients with disseminated germ-cell tumours do not attain complete remission with induction chemotherapy or relapse after such therapy. High-dose chemotherapy (HDC) plus autologous stem-cell rescue produces durable complete remission in these patients. This therapy is characterized by a high degree of haematological toxicity, although cardiac toxicity of some drugs used as part of HDC is also observed. We describe the case of a patient with refractory germ cell tumour, who was treated with HDC followed by autologous haematopoietic stem cell transplantation. The conditioning regimen was composed of cyclophosphamide, etoposide and carboplatin. Nine days after graft injection he developed cardiac complications and lower atrial rhythm. No clinical manifestations of these symptoms occurred. Neither renal-hepatic insufficiency nor disturbances of electrolytes were observed. Cyclophosphamide is probably the main perpetrator of cardiac toxicity in this patient. Its cardiotoxicity depends on cyclophosphamide dose and is caused by its active metabolites.